SC5 prone position ventilation: guidelines and checklist developed after simulation training in the rotherham foundation trust. (3rd November 2019) - Hormis, Anil; Jackson, Amanda; Dunn, Rachel; Chalk, Philippa
Abstract : Background: Recent publications in the critical care have shown the positive effects of turning a ventilated patient into the prone position following a diagnosis of Adult Respiratory Distress Syndrome (ARDS) to improve oxygenation and ventilation. This can be a complicated process in a critically ill patient attached to numerous infusion pumps and a ventilator. A simulation course was developed to help train the critical care nursing, physiotherapy and medical staff on the procedure. Summary of education programme: This was a multidisciplinary course, consisting of critical care nursing staff, senior respiratory physiotherapists, anaesthetic trainees and Consultant Intensivists. The teaching session comprised of a short power point presentation about the pathology and clinical presentation of ARDS, benefits of the prone position, physiotherapy management in the prone position, how to manage a patient in prone and a short video of how to turn a patient in this position. The 'proning checklist' was introduced at this stage. Three scenarios were carried out practically in the simulation suite that involved turning and managing a mannikin in a prone position. This included a critical incident. Debriefing was carried out after each scenario covering clinical and non technical skills aspects of the scenario by the senior faculty of the course. Results: Mean Likert scores showed: Aim and content of the session was clearly explained 4.93 The simulation felt realistic 4.11 Your knowledge and confidence has improved as a result of this session 4.80 Adequate time was given for the debrief/discussion 4.91 The session met with your educational needs 4.86 You felt equipped to care for a patient in the prone position, as a result of this session 4.66 Discussion: Feedback from the sessions showed that staff felt that they were more confident to turn a patient into prone safely and how to manage a patient in this position. They also found it extremely beneficial to train in a multidisciplinary team for this. Conclusions/Recommendations: The guidelines are now available on the Trust Intranet and the checklist has proved beneficial when preparing a patient to be turned and is available at each bedspace on the Critical Care Unit. We continue to run these sessions with new critical care staff and anaesthetics trainees and is now a mandatory course on our critical care unit.